The Correlations Between Serum Hcy Level and Seizures and Cognitive Function in Patients After Stroke. (14th December 2022) - Lan, Chen; Huang, Zhiqiang; Luo, Xinxin; Zhang, Yongcheng
Backgrounds: Post-stroke cognitive dysfunction (PSCI), a set of illnesses ranging from moderate cognitive impairment to dementia, which is one of the most prevalent consequences following a stroke. Homocysteine (Hcy) has been related to a number of neurological and systemic diseases. It's also a known risk factor for cardiovascular disease and systemic atherosclerosis (CVD). The link between Hcy and PSCI, on the other hand, is unknown. Methods: Our hospital evaluated 325 patients with acute cerebral infarction between January 1, 2018 and December 1, 2021. There are biological markers and baseline data available. Patients were divided into two groups based on the results of the Montreal Cognitive Assessment (MoCA). The researchers performed logistic regression analysis to find variables that may be linked to PSCI. Results: HCY levels were significantly higher in PSCI patients than in non-PSCI patients. Age, education, seizure manifestation, and income level were all shown to be independent risk variables for PSCI in a multivariate logistic analysis. Hcy levels in PSCI patients differed considerably between the high and low groups. The high and low Hcy levels groups had significantly varied hypertension histories and urine levels. Hcy levels in PSCI patients differed considerably between the high and low groups. The high and low Hcy levels groups had significantly varied hypertension histories and urine levels. Conclusion: Serum Hcy levels have been linked to PSCI in post-stroke patients, and researchers believe that serum Hcy levels will diminish PSCI.